Penerapan Model Pembelajaran Realistic Mathemathic Education (RMA) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V SD Negeri 03 Mamben Lauk - Sabahiyah, Sabahiyah; Wahyuni, Sri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research was motivated by the method used in teaching mathematics that did not involve students, and the teacher did not link the subject matter to the realities of everyday life so that students did not understand the material being studied. One effort to overcome this is by implementing a learning model that is related to the real world, namely the Realistic Mathematical Education (RME) learning model. The aim of this research is to improve students' critical thinking skills by applying the Realistic Mathematical Education (RME) learning model for class V SD Negeri 03 Mamben Lauk. This research is classroom action research, and was carried out over two cycles. Each cycle consists of four components, namely planning, acting, observing and reflecting. The subjects in this research were class V students at SD Negeri 03 Mamben Lauk with a total of 23 students, consisting of 10 boys and 13 girls. Data on students' critical thinking abilities was collected using written test techniques in the form of descriptions. Thinking ability data was analyzed descriptively. Based on the results of the analysis, it is known that the students' critical thinking skills in cycle I had a classical average of 73.47 and were in the medium category. Meanwhile in cycle II the classical average reached 82.83 and was in the high category. These results prove that the application of the Realistic Mathematics Education (RME) learning model can improve the critical thinking skills of class V students at SD Negeri 03 Mamben Lauk.